Modeling the Progenitor Stars of Observed Type IIP Supernovae - Kai-An You; Ke-Jung Chen; Yen-Chen Pan; Sung-Han Tsai; Po-Sheng Ou (The Astrophysical Journal, 2024)
Type IIP supernovae (SNe IIP) are thought to originate from the explosion of massive stars >10 M _⊙ . Their luminosity is primarily powered by the explosion energy and the radioactive decay energy of ^56 Co, with the photosphere location regulated by hydrogen recombination. However, the physical connections between SNe IIP and their progenitor stars remain unclear. This paper presents a comprehensive study of SNe IIP and their progenitor stars by using the one-dimensional stellar evolution code, MESA . Our model grids consider the effects of stellar metallicity, mass, and rotation in the evolution of massive stars, as well as the explosion energy and ^56 Ni production in modeling supernovae. To elucidate the observed SNe IIP and their origins, we compare their light curves (LCs) with our models. Furthermore, we investigate the impact of stellar parameters on LCs by considering stellar mass, metallicity, rotation, explosion energy, and ^56 Ni production. We find that more massive stars exhibit longer plateaus due to increased photon diffusion time caused by massive ejecta. Higher metallicity leads to increased opacity and mass loss of progenitor stars. Rapid rotation affects internal stellar structures, enhancing convective mixing and mass loss, potentially affecting the plateau’s brightness and duration. Higher explosion energy results in brighter but shorter plateaus due to faster-moving ejecta. ^56 Ni mass affects late-time luminosity and plateau duration, with larger masses leading to slower declines.